“reducción de costos operativos mediante la estandarización de malla de perforación - voladura, para labores horizontales: sección 4.0 m. x 4.0 m., mina socorro - uchucchacua.” - Correa Namoc, Luis Jhonatan (2016)
This thesis is entitled "Reducing operating costs by standardizing Malla Drilling - blasting, Horizontal for work: Section 4.0 M x 4.0 M, Mina Socorro - Uchucchacua." And its active target show that it is possible to reduce operating costs A to drilling and blasting mesh standardization using standards of the unit mining operations OPTIMOS work that they are the drilling, blasting, loading, transport and maintenance, the pursuit of stability and success in the mining cycle. With this thesis we seek FINDING A standard mesh, for the most economically profitable reserves the operation; Paragraph begins Research defined study population consisting of 4 horizontal working, Gallery 665 (Gal665), Cruise 7296 (Cx7296), Cruise 7200 (Cx7200) and Cruise 7424 (Cx7424). Initially Background These tasks, daily reports as explosives poll Order vouchers, among others, will be sought. UN is gathering information Perform cycle of mining in the ESA work, analysis of costs Operations Unit drilling, blasting, loading, hauling and support. Then we found standardize drilling and blasting mesh and implement paragraph feed · analyze the costs in each of the unit operations. Finally, we make a contrast of the above costs with the costs obtained with the implementation of the proposed mesh where the benefits obtained by the application of the mesh, reducing costs without increases standard exposed.